Stability of Hemostasis Parameters in Whole Blood, Plasma, and Frozen Plasma: Literature Review and Recommendations of the SFTH (French Society of Thrombosis and Haemostasis) - Flaujac, Claire; Delassasseigne, Céline; Hurtaud-Roux, Marie-Françoise; Delahousse, Benedicte; Boissier, Elodie; Desconclois, Céline; the Working Group on Preanalytics in the French Society of Thrombosis Haemostasis (Seminars in Thrombosis and Hemostasis, 2024)
Preanalytical sample management is critical for a proper assessment of hemostasis parameters, and may differ depending on prescribed tests or additional tests considered to be necessary after initial results. Although there is quite vast literature on this issue, the Working Group of the French Society of Thrombosis and Haemostasis (SFTH) deemed it necessary to make an in-depth literature review and propose recommendations for the proper handling of samples prior to hemostasis assays. This extensive assessment is accessible on-line in French at the SFTH website. Here, a more synthetic view of these recommendations is proposed, supported by easy-to-use tables. The latter respectively deal with the stability of whole blood or fresh plasma, frozen samples, and proper handling of samples forwarded on dry ice. Procedures are classified as recommended, acceptable, not conformed and lacking data. This work involved the retrieval of 125 references, first screened by a working group of 6 experts, then reviewed by 20 other experts in the field. The highly detailed conditions summarized in these tables will hopefully help hemostasis laboratories to secure the conditions recommended for sample collection and transportation. Moreover, as some conditions clearly lacked recommendations, this review can open new fields of investigation for hemostasis preanalytics.
Keywords: stability; blood coagulation factors; anticoaguant; fresh frozen plasma